2021
DOI: 10.21926/rpm.2102016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Durability of Bio-based Earth Composites

Abstract: Bio-based earth composites present various environmental benefits, such as usable wastes, coproducts, abundant or renewable materials, etc. Moreover, the incorporation of bioaggregates in the earth matrix allows the buildings to act as an effective carbon sink. A growing number of studies are now focusing on the mechanical and hygrothermal properties of bio-based earth building materials. However, the durability of these types of material is a major concern, and knowledge of their various aspects is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…En lo que respecta a las muestras de revoque grueso, tanto su densidad como λ son similares a los de las muestras de adobe. Esta similitud se atribuye a que, independientemente de los materiales empleados (paja para los adobes y arena + paja para el revoque grueso), la relación agua/tierra de ambos, principal causante de la porosidad y densidad aparente de los elementos constructivos de tierra (Laborel-Préneron et al, 2018), son iguales, de 0.34. Del mismo modo, las muestras de revoque fino con una relación agua/ tierra de 0.47 -la mayor después de la del relleno de quincha-presentan luego la menor densidad y λ promedio.…”
Section: Paquete Constructivounclassified
“…En lo que respecta a las muestras de revoque grueso, tanto su densidad como λ son similares a los de las muestras de adobe. Esta similitud se atribuye a que, independientemente de los materiales empleados (paja para los adobes y arena + paja para el revoque grueso), la relación agua/tierra de ambos, principal causante de la porosidad y densidad aparente de los elementos constructivos de tierra (Laborel-Préneron et al, 2018), son iguales, de 0.34. Del mismo modo, las muestras de revoque fino con una relación agua/ tierra de 0.47 -la mayor después de la del relleno de quincha-presentan luego la menor densidad y λ promedio.…”
Section: Paquete Constructivounclassified
“…The least erosive mixture with SDP and CHP was 2.5%, whereas the best performance with ESP was obtained with the mixture with 40% ESP. The good cohesion between waste particles and clay prevents water from penetrating the sample and clay particles from washing away by water which appears to be the explanation for the sample's good performance [155].…”
Section: Dripmentioning
confidence: 99%
“…Researchers conducted experiments 58 using sawdust for manufacturing different types of 59 building materials [60]. Some of the developed 60 materials include particleboard [61][62][63][64][65], insulation 61 material [66], cement concrete brick [67,68], fired clay 62 brick [58,[69][70][71][72][73] and unfired brick [24,48,[74][75][76][77][78][79][80]. 30 were carefully cleaned with a cloth to eliminate any loose substance attached.…”
Section: Introductionmentioning
confidence: 99%
“…Countable studies dealt with the fire behavior of earthen material. Some agreed that earthen materials have an insulation property allowing them to prevent heat spreading after testing the temperature of earth block's unexposed face in an oven at 800°C for two hours, and with a property to not ignite themselves when subjecting them to a radiator heat source for ignition time and extinguishability tests (Préneron et al, 2017). Others concluded that rammed earth materials can remain intact during and after heating with unidirectional heat fluxes of 20, 35 and 50 kW.m -2 (Beckett et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…cm from the bottom of the furnace opening (20 cm x 20 cm) and 1 cm from the heated face of the tested samples to record temperatures into the furnace. During the test, gas pressure was manually Construction Technologies and Architecture Vol 1. …”
mentioning
confidence: 99%